2018
DOI: 10.1111/jace.16015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of yttria and magnesia on densification and thermal conductivity of sintered reaction‐bonded silicon nitrides

Abstract: A variety of combinations of Y2O3 and MgO were used as additives in preparing Si3N4 ceramics by the sintering of reaction‐bonded silicon nitride (SRBSN) method. By varying the amount of Y2O3 in the range of 0‐5 mol% and that of MgO in the range of 0‐8 mol%, the effects of Y2O3 and MgO additives on nitridation and sintering behaviors as well as thermal conductivity were studied. It was found that appropriate amount and combination of Y2O3 and MgO additives were essential for attaining full densification and ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 22 publications
(31 reference statements)
2
28
0
Order By: Relevance
“…The ZrO 2 in 3Z4M was produced by the reaction between SiO 2 and ZrSi 2 , thus the glassy phase was reduced due to the consumption of SiO 2 (6) by ZrSi 2 . Besides, a significant difference in microstructure of ZrSi 2 -doped samples with some literature, 41,[45][46][47] also the most interesting one, is that the distribution state of the grain boundary phase and the thickness of grain-boundary film according to the high-magnification observations. The secondary phases were enriched at triple and multiple junctions and the grain boundary film was extremely thin in densified samples indicating a higher Si 3 N 4 -Si 3 N 4 contiguity.…”
Section: Microstructurementioning
confidence: 99%
“…The ZrO 2 in 3Z4M was produced by the reaction between SiO 2 and ZrSi 2 , thus the glassy phase was reduced due to the consumption of SiO 2 (6) by ZrSi 2 . Besides, a significant difference in microstructure of ZrSi 2 -doped samples with some literature, 41,[45][46][47] also the most interesting one, is that the distribution state of the grain boundary phase and the thickness of grain-boundary film according to the high-magnification observations. The secondary phases were enriched at triple and multiple junctions and the grain boundary film was extremely thin in densified samples indicating a higher Si 3 N 4 -Si 3 N 4 contiguity.…”
Section: Microstructurementioning
confidence: 99%
“…It was consistent with previously reported results that high MgO content led to a decrease of the density of the samples. 51,52 When the MgO combined with Y 2 O 3 as sintering additives, the role of MgO was to reduce the viscosity of the liquid Figure 7 showed the fracture toughness and flexural strength of Si 3 N 4 ceramics sintered at 1900 • C for 4 h with different Y 2 O 3 /MgO ratios, respectively. The sample 0Y7M with the lowest fracture toughness and flexural strength was obtained, while the samples 1Y6M, 2Y5M, 3Y4M, and 4Y3M showed good mechanical properties because the microstructure of them showed that the long rod-like β-Si 3 N 4 grains distributed in fine β-Si 3 N 4 grains to form bimodal morphology, which was conducive to the flexural strength.…”
Section: Effect Of Y 2 O 3 /Mgo Ratio On Thermal Conductivity and Mec...mentioning
confidence: 99%
“…In this study, we focus on the relation between the lattice constant and the lattice oxygen content of the β ‐Si 3 N 4 crystal included in the sintered reaction‐bonded silicon nitride (SRBSN) ceramics 18,23–29 with the aim of realizing nondestructive measurement of the lattice oxygen content, which would be easier than employing the hot‐gas extraction method that necessitates grinding, acid treatment, and pyrolysis of the ceramic sample. Wang et al reviewed the relation between the lattice parameter and the oxygen content in regard to an α ‐Si 3 N 4 crystal made by various methods, including chemical vapor deposition, and reported that the lattice volume increases with the decrease in the oxygen content 11 .…”
Section: Introductionmentioning
confidence: 99%